A Novel P-III Metalloproteinase from Bothrops barnetti Venom Degrades Extracellular Matrix Proteins, Inhibits Platelet Aggregation, and Disrupts Endothelial Cell Adhesion via α5β1 Integrin Receptors to Arginine–Glycine–Aspartic Acid (RGD)-Containing Molecules - Pedro Henrique de Caires Schluga; Debora Larangote; Ana Maria de Melo; Guilherme Kamienski Lobermayer; Daniel Torrejón; Luciana Souza de Oliveira; Valeria Gonçalves Alvarenga; Dan Erick Vivas-Ruiz; Silvio Sanches Veiga; Eladio Flores Sanchez; Luiza Helena Gremski (Toxins)
Viperid snake venoms are notably abundant in metalloproteinases (proteins) (SVMPs), which are primarily responsible for inducing hemorrhage and disrupting the hemostatic process and tissue integrity in envenomed victims. In this study, barnettlysin-III (Bar-III), a hemorrhagic P-III SVMP, was purified from the venom of the Peruvian snake Bothrops barnetti. Bar-III has a molecular mass of approximately 50 kDa and is a glycosylation-dependent functional metalloproteinase. Some biochemical properties of Bar-III, including the full amino acid sequence deduced from its cDNA, are reported. Its enzymatic activity is increased by Ca2+ ions and inhibited by an excess of Zn2+. Synthetic metalloproteinase inhibitors and EDTA also inhibit its proteolytic action. Bar-III degrades several plasma and ECM proteins, including fibrin(ogen), fibronectin, laminin, and nidogen. Platelets play a key role in hemostasis and thrombosis and in other biological process, such as inflammation and immunity, and platelet activation is driven by the platelet signaling receptors, glycoprotein (GP)Ib-IX-V, which binds vWF, and GPVI, which binds collagen. Moreover, Bar-III inhibits vWF- and convulxin-induced platelet aggregation in human washed platelets by cleaving the recombinant A1 domain of vWF and GPVI into a soluble ectodomain fraction of ~55 kDa (sGPVI). Bar-III does not reduce the viability of cultured endothelial cells; however, it interferes with the adhesion of these cells to fibronectin, vitronectin, and RGD peptides, as well as their migration profile. Bar-III binds specifically to the surface of these cells, and part of this interaction involves α5β1 integrin receptors. These results contribute to a better comprehension of the pathophysiology of snakebite accidents/incidents and could be used as a tool to explore novel and safer anti-venom therapeutics.